Electric Arc Synthesis of Titanium Carbide Using Carbon Obtained by the Thermal Conversion of Food Industry Wastes - Svinukhova A. A. Arina Andreevna; Yankovsky S. A. Stanislav Aleksandrovich; Misyukova A. D. Albina Dmitrievna; Pak A. Ya. Aleksandr Yakovlevich (2024, 2024)
Title screen